Absence of histamine-induced itch in the African naked mole-rat and "rescue" by Substance P - Lewin Gary R; Blass Gregory RC; Smith Ewan; Park Thomas J (SAGE Publishing, 2010)
Abstract Recent research has proposed a pathway in which sensory neurons expressing the capsaicin activated ion channel TRPV1 are required for histamine-induced itch and subsequent scratching behavior. We examined histamine-induced itch in the African naked mole-rat (Heterocephalus glaber) and found that although naked mole-rats display innate scratching behavior, histamine was unable to evoke increased scratching as is observed in most mouse strains. Using calcium imaging, we examined the histamine sensitivity of naked mole-rat dorsal root ganglia (DRG) neurons and identified a population of small diameter neurons activated by histamine, the majority of which are also capsaicin-sensitive. This suggested that naked mole-rat sensory neurons are activated by histamine, but that spinal dorsal horn processing of sensory information is not the same as in other rodents. We have previously shown that naked mole-rats naturally lack substance P (SP) in cutaneous C-fibers, but that the neurokinin-1 receptor is expressed in the superficial spinal cord. This led us to investigate if SP deficiency plays a role in the lack of histamine-induced scratching in this species. After intrathecal administration of SP into the spinal cord we observed robust scratching behavior in response to histamine injection. Our data therefore support a model in which TRPV1-expressing sensory neurons are important for histamine-induced itch. In addition, we demonstrate a requirement for active, SP-induced post-synaptic drive to enable histamine sensitive afferents to drive itch-related behavior in the naked mole-rat. These results illustrate that it is altered dorsal horn connectivity of nociceptors that underlies the lack of itch and pain-related behavior in the naked mole-rat.